Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan pada KUD PAKIS KAB. Malang - Baihaki, Ahmad; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study investigates the influence of motivation and work discipline on employee performance in KUD Pakis, Malang Regency. The research variables consist of Motivation (X1) and Work Discipline (X2) as independent variables and Employee Performance (Y) as the dependent variable. The findings suggest that partial regression analysis indicates a significant influence of Motivation (X1) on Employee Performance (Y), while Work Discipline (X2) does not show a significant influence on Employee Performance (Y). Moreover, simultaneous regression analysis reveals that both Motivation (X1) and Work Discipline (X2) have a significant influence on Employee Performance (Y). Keywords: Motivation, Discipline, Performance, Partial Regression, Simultaneous Regression